Acoustic wave damping anisotropy in nematic liquid crystals - HERBA, H.; DRZYMAŁA, A. (Archives of Acoustics, 1992)
This paper presents the results of damping and velocity measurements of an ultrasonic wave with 5 MHz frequency performed in two nematic liquid crystals: pentylcyanobiphenyl (PCB) and 4-n-methoxybenzoate-4-n-pentylphenyl. Measurements were carried out in materials oriented with an external magnetic field. An acoustic wave damping anisotropy was observed. It manifested itself with a dependence between the damping coefficient and angle between the direction of wave propagation and the direction of the magnetic field which orientates the material. The obtained results were confronted with the results of rheological measurements carried out for mentioned materials by other authors.